Implementation of Law Number 2 of 2002 on Legal Protection of Traffic Accident Victims - Wafiq Zahrani Boulu (Cattleya Darmaya Fortuna, 2025)
This study aims to analyze the implementation of Law Number 2 of 2002 related to legal protection for victims of traffic accidents in the jurisdiction of the Gorontalo City Police Traffic Unit. The method used is an empirical normative approach, with a focus on case studies that combine normative legal data with the reality of practice in the field. Primary data was obtained through direct research at the Sub-Directorate of Law Enforcement of the Gorontalo City Police, while secondary data included primary legal materials such as Law Number 22 of 2009 concerning Road Traffic and Transportation as well as secondary sources in the form of scientific books, legal journals, and the views of experts. The results of the study revealed that legal protection for victims is carried out through two main approaches. The preventive approach is carried out by providing education through socialization in the school environment and vehicle communities, as well as through the installation of billboards on a number of roads. The repressive approach is applied through the restorative justice mechanism before taking the litigation route, and if mediation fails, the case is resolved in court openly. The study also identified two main obstacles in the legal protection process: first, delays in reporting by victims which often occur a few days after the accident; Second, lack of witness participation due to concerns about legal proceedings or personal inconvenience. Therefore, increasing legal understanding among the community and strengthening collaboration between the police and residents is crucial in creating more effective and responsive legal protection in Gorontalo City.